Perceptions and practices related to menstruation amongst tribal adolescent girls in rural field practice area of tertiary health care institute in Mumbai - Meshram, Pravin Dilipkumar; Ratta, Amandeep Kaur; Kumar, Vinod (International Journal Of Community Medicine And Public Health, 2020)
Background: Adolescence is the crucial phase in the woman’s life has on the woman’s health and later on reproductive and maternal life. Around 20% of the global health burden among women is attributed to reproductive and sexual ill health, lack of menstrual hygiene is one of the factors among the adolescent. They lack awareness about menstruation when they first experience it, especially in rural and tribal areas. This study aimed to provide an insight into the most sensitive issue of menstruation among the tribal community which would help in promoting improved awareness level and increase in right knowledge about menstruation. Methods: A cross sectional study. Total of 114 adolescent girls (11-18 years), have attained the menarche were included. Universal sampling method is used. Data was collected regarding their perceptions and practices related to menstrual hygiene. Results: The mean age of the subjects and of menarche were 15.48±1.75, 13.09±1.04 years respectively. About 27.20% had no clue about the menstrual cycle. Majority of them asked their mothers about the problems followed by close friends. About 37.72% used sanitary napkins. Not to attend religious occasion (54.39%) was common restriction. Conclusions: In the present study, it is reflected that mothers of the adolescent girls were a crucial and important role in giving information about menstrual hygiene. More awareness related to hygiene and practice and education related to social issues related to menstrual hygiene has to be addressed. Focussed programmes related to tribal adolescent health have to be implemented.